The TBLR1/TBL1 co-factor complex acts as a transcriptional checkpoint in the brown adipose tissue response to prolonged cold exposure - Köker, Sahika Cingir; Tsokanos, Foivos-Filippos; El-Merahbi, Rabih; Jha, Ankush Kumar; Cicatelli, Karin; Weber, Peter; Mhamane, Amit; Kaltenecker, Doris; Morigny, Pauline; Loft, Anne; Klepac, Katarina; Maida, Adriano; et al. (The FASEB journal, 2025)
Brown adipose tissue (BAT) is a key thermogenic organ, whose activation in response to cold environmental temperatures and β-adrenergic stimulation requires the proper function of the NCOR/HDAC3 corepressor complex in brown adipocytes. The NCOR/HDAC3 complex is large and multi-component, including the transducin beta-like 1 (TBL1) and TBL1-related 1 (TBLR1) proteins. Loss of TBL1 in the hepatocytes and TBLR1 in the white adipocytes has been shown to impair fasting- and β-adrenergic-induced lipolysis. However, their roles in BAT thermogenesis remain unknown. Here, we report that deletion of TBLR1 alone in brown adipocytes does not impair the adaptive thermogenic response to prolonged cold exposure. In contrast, simultaneous deletion of TBL1 and TBLR1 dampens β-adrenergic-induced lipolysis and mitochondrial respiration in cultured mouse brown adipocytes. Transgenic mice with UCP1-Cre mediated double deletion of TBLR1 and TBL1 exhibit reduced whole-body energy expenditure during prolonged cold exposure, lower core body temperature, increased appearance of unilocular adipocytes in BAT, and suppressed expression of metabolic and myogenic PRDM16 target genes. Also, we present some evidence that TBLR1 and TBL1 interact with HDAC3 and PRDM16 in brown adipocytes, potentially suggesting a direct involvement in the PRDM16-controlled transcriptional program. These findings identify the TBLR1/TBL1 complex as a critical regulator of BAT adaptation to prolonged cold and systemic energy homeostasis, shedding light on the context-dependent functions of corepressor complexes.